Clutter and terrain effects on path loss in the VHF/UHF bands. Issue 1 (8th December 2017) - Faruk, Nasir; Bello, Olayiwola W.; Oloyede, Abdulkarim A.; Surajudeen‐Bakinde, Nazmat T.; Obiyemi, Obiseye; Olawoyin, Lukman A.; Ali, Maaruf; Jimoh, Abdulhameed
Abstract : Path loss models are essential in the planning of wireless networks. However, the peculiar ambient characteristics of geographical locations necessitate a wide range of these models to take into consideration the different terrain dielectric, scattering irregularities, and clutter. This study investigates the effects of terrain and clutter on frequency‐dependent path loss models in the very high frequency (VHF) and ultra high frequency (UHF) bands using multi‐transmitter scenarios. Seven transmitters and 15 measurement routes were covered using an Agilent N9342C spectrum analyser. The measured results show that the models' prediction errors (PEs) follow the terrain profile and also that the clutter effects are noticeable along each route with varying degrees of impact. Near constant standard deviation errors (SDEs) were observed across all the models for the specific routes as well as a strong dependency on the terrain profile and clutters along the measurement routes. The UHF and VHF bands have average SDEs of 10.5 and 7.5 dB, respectively. A three‐dimensional digital elevation model (DEM) showing the terrain and PE was also developed. Contour lines were extracted from the advanced spaceborne thermal emission radiometer and global DEM data sets. Visualisation of the terrain profile was achieved in the ArcScene software environment.